2023
DOI: 10.3390/eng4010039
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Machine Learning Techniques for Accurate and Efficient Detection of Botnet Attacks in Connected Computers

Abstract: The transmission of information, ideas, and thoughts requires communication, which is a crucial component of human contact. The utilization of Internet of Things (IoT) devices is a result of the advent of enormous volumes of messages delivered over the internet. The IoT botnet assault, which attempts to perform genuine, lucrative, and effective cybercrimes, is one of the most critical IoT dangers. To identify and prevent botnet assaults on connected computers, this study uses both quantitative and qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Afrifa et al [17] start with the assumption that significant numbers of IoT devices are regularly commandeered into botnets by malicious actors to further nefarious goals that threaten global commerce. Due to resource constraints of typical IoT devices, a single compromised device may not be particularly dangerous, but a botnet comprised of thousands or millions of compromised devices can cause significant harm.…”
Section: Related Workmentioning
confidence: 99%
“…Afrifa et al [17] start with the assumption that significant numbers of IoT devices are regularly commandeered into botnets by malicious actors to further nefarious goals that threaten global commerce. Due to resource constraints of typical IoT devices, a single compromised device may not be particularly dangerous, but a botnet comprised of thousands or millions of compromised devices can cause significant harm.…”
Section: Related Workmentioning
confidence: 99%
“…To assess the efficacy of the HM techniques, the RMSE, MAE, MAPE, and coefficient of determination (R 2 ) were utilised in this study. When RMSE and MAE decline and R 2 approaches one, the performance of HM strategies improves [45,46]. MAPE is an alternative statistical metric for evaluating a regression model's accuracy in terms of discrepancies between observed and predicted values.…”
Section: Statistical Analysis and Evaluation Metricsmentioning
confidence: 99%
“…Its disadvantage is that, due to its high false-positive rates, it is not a simple structure. Afrifa et al 43 demonstrated a method for precise and successful botnet attack detection in connected devices using ensemble machine-learning techniques. They employed the stacking ensemble technique and a decision tree classifier to identify botnets in computer network traffic with 99% accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%